Preoperative somatostatin analogues versus direct transsphenoidal surgery for newly-diagnosed acromegaly patients: a systematic review and meta-analysis using the GRADE system - Nunes, V. S. [UNESP]; Correa, J. M. S. [UNESP]; Puga, M. E. S.; Silva, E. M. K.; Boguszewski, C. L. (Springer, 2015)
Whether the preoperative use of somatostatin analogues (SA) improves surgical outcomes in acromegaly is still a matter of debate.We conducted a systematic review of randomized, controlled trials that compared the short-term outcomes of preoperative use of SA (Pre-SA) with direct TSS (No-SA) for the treatment of newly diagnosed acromegaly.Embase, Pubmed, Lilacs, and Central Cochrane were used as our data sources. The primary outcomes were no need for any adjuvant treatment 3 months after surgery, based on biochemical results (GH nadir after OGTT < 1 mu g/L and normal IGF-1 for age and gender), quality of life and mortality. The included trials were analyzed using the Grading of Recommendations Assessment, Development, and Evaluation approach.A total of 2.099 references were identified and two reviewers independently screened the titles and abstracts. From the 14 potentially eligible studies, four were included and ten were excluded due to lack of randomization or different outcomes. A pool of 261 patients was randomly assigned to Pre-SA or No-SA. Meta-analysis of IGF1 normalization showed a significant difference in favor of Pre-SA (RR 2.47; 95 % CI 1.66, 3.77). Adding a GH nadir on OGTT a parts per thousand currency sign1 mu g/L, we found a RR of 2.15 (95 % CI 1.39, 3.33). Quality of evidence for no need of adjuvant postoperative treatment was moderate, but for improving quality of life was very low and for mortality was absent.Pre-SA increases the chance of biochemical control of acromegaly 3 months after TSS in patients harboring GH-secreting pituitary macroadenomas.
Keywords: Acromegaly; Somatostatin analogues; Systematic review; Meta-analysis